LPS induces ALOX5 promoter activation and 5-lipoxygenase expression in human monocytic cells. (March 2020) - Poirier, Samuel J; Boudreau, Luc H; Flamand, Nicolas; Surette, Marc E
Highlights: LPS induces human monocytic cell maturation and increased leukotriene biosynthesis. Leukotriene biosynthesis is associated with increased 5-lipoxygenase expression. The first report of agonist-induced ALOX5 promoter activation in human leukocytes. New insight on mechanisms of 5-lipoxygenase regulation in immature leukocytes. Abstract: 5-lipoxygenase (5-LO), coded by the ALOX5 gene, is expressed in leukocytes and catalyzes the formation of leukotrienes, pro-inflammatory lipid mediators. Leukotrienes are central to immune responses, but are also involved in inflammatory disorders and 5-LO expression is associated with leukemia stem cell survival. It is therefore important to understand mechanisms that control 5-LO expression. This study investigated the control of 5-LO expression and leukotriene biosynthesis following the maturation of human monocytic cells. MonoMac-1 (MM1) and THP-1 cells were incubated for up to 72 h with or without LPS and TGF-β. LPS, but not TGF-β, increased CD14 expression in both MM1 and THP-1 cells. Incubation with LPS (100 ng/ml) and TGF-β (1 ng/ml) synergistically increased the capacity of MM1 cells to produce 5-LO products from undetectable levels to 40±5 pmol/10 6 cells. 5-LO product biosynthesis in THP-1 cells increased 25-fold. A synergistic effect of LPS and TGF-β was measured with increases in 5-LO mRNA of 54- and 13-fold in MM1 and THP-1 cells, respectively. 5-LO protein expression increased significantly in both MM1 and THP-1 cells. ALOX5 promoter activity was significantly elevated >2-fold in both cell lines following LPS treatment, but TGF-β was without effect. The main 5-LO products were cysteinyl-leukotrienes, however LPS and TGF-β did not impact on the capacity of the cells to metabolize leukotriene A4 . Overall, this study demonstrates that receptor-mediated stimulation of MM1 and THP-1 cells by LPS is associated with increased 5-LO expression. This represents a new mechanism by which leukotriene biosynthesis can be modulated by pathological agents.